Phylum Onychophora Grube, 1853. In: Zhang, Z.-Q. (Ed.) Animal Biodiversity: An Outline of Higher-level Classification and Survey of Taxonomic Richness (Addenda 2013) - Mayer, Georg; Oliveira, Ivo De Sena (Zootaxa, 2013)
Extant representatives of Onychophora (velvet worms) have been classified into two major subgroups or families, the Peripatidae and the Peripatopsidae. According to our previous estimate, a total of 179 nominal species and twelve additional infraspecific taxa of Onychophora had been described, including numerous “subspecies”, “variations” and “mutations (Mayer & Oliveira 2011). However, the validity of most of these taxa was uncertain. Since this last estimate, a comprehensive world checklist of Onychophora has been published, along with a revision of the nomenclatural status of names (Oliveira et al. 2012a). This study revealed that many previous synonyms and infraspecific taxa might constitute valid species. At the same time, it also has shown that 10% of the described species of Onychophora show major taxonomical problems and therefore should be regarded as nomina dubia, following the provisions of the International Code of Zoological Nomenclature (ICZN 1999).